2019
DOI: 10.3847/2041-8213/ab4517
|View full text |Cite
|
Sign up to set email alerts
|

The Star Formation History and Dynamics of the Ultra-diffuse Galaxy Dragonfly 44 in MOND and MOG

Abstract: The observed line-of-sight velocity dispersion σ los of the ultra diffuse galaxy Dragonfly 44 (DF44) requires a Newtonian dynamical mass-to-light ratio of M dyn /L I = 26 +7 −6 Solar units. This is well outside the acceptable limits of our stellar population synthesis (SPS) models, which we construct using the integrated galactic initial mass function (IGIMF) theory. Assuming DF44 is in isolation and using Jeans analysis, we calculate σ los profiles of DF44 in Milgromian dynamics (MOND) and modified gravity (M… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 77 publications
12
31
0
Order By: Relevance
“…Our results are also in line with Webster et al (2015), showing that the shortest SFT required for the observed self-enrichment of the UFDs is about 0.1 Gyr. The gas of low-mass-satellite galaxies was removed by their interaction with the Milky May (Romano et al 2015(Romano et al , 2019 such that they shut off star formation on a short timescale, as also found for Dragonfly 44 by Haghi et al (2019).…”
Section: Star Formation Historymentioning
confidence: 64%
See 1 more Smart Citation
“…Our results are also in line with Webster et al (2015), showing that the shortest SFT required for the observed self-enrichment of the UFDs is about 0.1 Gyr. The gas of low-mass-satellite galaxies was removed by their interaction with the Milky May (Romano et al 2015(Romano et al , 2019 such that they shut off star formation on a short timescale, as also found for Dragonfly 44 by Haghi et al (2019).…”
Section: Star Formation Historymentioning
confidence: 64%
“…The chemical abundance of the dwarf galaxy combined with the IGIMF theory (i.e. a computed top-light gwIMF) suggests a short SFT of about 0.1 Gyr (similar to the dwarf galaxy Dragonfly 44, Haghi et al 2019). This not only agrees well with the stellar synthesis study of Boötes I (Brown et al 2014), but is also self-consistent with the empirical gas-depletion timescale of galaxies when the IGIMF theory is assumed (Pflamm-Altenburg & Kroupa 2009).…”
Section: Resultsmentioning
confidence: 94%
“…MOG is a covariant scalar-tensor-vector gravity theory which allows the gravitational constant G, a vector field coupling ω, and the vector field mass µ to vary with space and time. This model was recently ruled out at 5.49σ using the velocity dispersion profile of the ultra-diffuse galaxy Dragonfly 44 (Haghi et al 2019). While perhaps the basic ideas of MOG can still be saved by applying some corrections or modifications, its current formulation seems to be in conflict with observations.…”
Section: A Lower Massmentioning
confidence: 99%
“…However, including the Galactic external field did not much improve the agreement with observations (Derakhshani & Haghi 2014). MOND can also explain the velocity dispersion of the ultra-diffuse galaxy Dragonfly 2 (DF2, Kroupa et al 2018b), DF4 (Haghi et al 2019a), and DF44 (Bílek et al 2019), with the latter galaxy having a measured dispersion profile that is consistent with MOND at 2.40σ (Haghi et al 2019b). The calculations for DF2 and DF4 are significantly affected by the EFE.…”
Section: Introductionmentioning
confidence: 69%